Doping-induced microstructural, textural and optical properties of In2Ti1-xVxO5+delta semiconductors and their role in the photocatalytic splitting of water - Shah, Pallavi; Bhange, Deu S.; Deshpande, Aparna; Kulkarni, Mukund S.; Gupta, Narendra M. (Materials Chemistry and Physics, 2009)
The physicochemical properties of V-doped indium titanates (In2Ti1-xVxO5-delta, 0.0 <= x <= 0.2) were investigated by using XPS, powder XRD, UV-vis, SEM and luminescence spectroscopy techniques. The Rietveld refinement of XRD data revealed that even though the V-containing samples were isostructural with In2TiO5 (orthorhombic space group Pnma), a systematic x-dependent variation was noticeable in the Ti-O bond lengths in [TiO6] octahedral units, cell parameters and in the value of delta. XPS results confirmed the coexistence of V5+ and V4+ states, leading thereby to an enhancement in oxygen non-stoichiometry in the doped samples. A loading-dependent progressive shift from 400 to 750 nm was also observed in the onset of the absorption edge, indicating a significant narrowing of the band gap. Furthermore, the samples with higher V-content were comprised of the grain clusters having larger size and an irregular shape. The UV-vis. photoluminescence and thermoluminescence studies indicate that the doping-induced lattice defects may give rise to certain closely spaced acceptor/donor energy levels in between the band gap of host matrix. The indium titanates are found to serve as stable photocatalysts for water splitting under visible light, where oxygen was the major reaction product. The role of microstructural and morphological properties in the photocatalytic activity is discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: In2Ti1-xVxO5+delta photocatalysts; Luminescence spectroscopy; Microstructure; Optical properties; Structure-activity relationship; water splitting

Critical role of particle size and interfacial properties in the visible light induced splitting of water over the nanocrystallites of supported cadmium sulphide - Deshpande, Aparna; Gupta, Narendra M. (International Journal of Hydrogen Energy, 2010)
CdS crystallites of varying size (1 to 5.0 nm) were successfully deposited on the surfaces of polyester and activated charcoal. The size and the texture of these crystallites depended on CdS loading and also on the substrate morphology. These highly dispersed photocatalysts displayed a pyramidal trend in activity for visible light induced splitting of water molecules, similar to that reported for the heterogeneous catalytic reactions over supported noble metals. Thus, the CdS particles of similar to 2.5 nm size gave rise to maximum rate of H(2) evolution as compared to the particles of either smaller or of larger size. The particles of <1.5 nm diameter were of poor crystallinity and displayed a significant Q-size effect on the absorption edge. Our study provides direct evidence for the structure sensitivity of photocatalytic dissociation of water over supported semiconductor nanocrystallites, where the particle size and the interfacial microstructural defects played a vital role. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS nanocrystallites; Interfacial defects; Photocatalysis; Structural sensitivity; water splitting

Influence of zeolitic structure on photoreduction property and hydrogen evolution reaction - Chatti, Ravikrishna V.; Dubey, Nidhi; Joshi, Meenal V.; Labhsetwar, Nitin K.; Joshi, P. N.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
A new photocatalytic material developed by supporting TiO(2) in combination with transition metal ion like cobalt and heteropolyacid (HPA) on the surface is facilitating enhanced photoreduction of water and methyl orange Zeolites being a solid acid play an important role in the electron transfer reaction, facilitated by the Lewis acid sites in the form of aluminium ions In the present work, four different zeolite matrices namely, NaY zeolite, ultrastable zeolite Y, beta zeolite and titanium silicate-1 have been used for the synthesis of new photocatalytic materials These materials have been evaluated for water splitting by an initial screening procedure using methyl orange photoreduction The photocatalyst containing Na Y has emerged as a potential photocatalyst with hydrogen evolution rate of 2730 mu mol/h/g of TiO(2) Hydrogen evolution was not observed for the composite photocatalysts synthesized using the other zeolite matrices It has been observed that physicochemical properties like Si/Al ratio, acidity and basicity of the zeolite support have a tremendous influence on the photoreduction property of these zeolite matrices (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: H(2) evolution; Lewis acidity; Si/Al ratio; water splitting; Zeolite structure

Factors affecting the production of H-2 by water splitting over a novel visible-light-driven photocatalyst GaFeO3 - Dhanasekaran, P.; Gupta, N. M. (International Journal of Hydrogen Energy, 2012)
A d(10) photocatalyst, GaFeO3 having a band gap of similar to 2.7 eV, exhibits significant activity for the overall splitting of water under visible light (>395 nm) irradiation, in the absence of sacrificial reagent or a noble metal co-catalyst. The doping of an anion led to considerable enhancement in activity, the S-doped catalysts displaying better activity compared to the samples containing nitrogen. Even though the H-2/O-2 yields were affected by preparation-dependent grain morphology, no direct relationship was observed between the photoactivity of a sample and its specific surface area. The techniques of HRTEM, SEM, XPS, Laser Raman, UV-visible and photoluminescence spectroscopy have enabled to demonstrate that, besides the grain morphology, certain lattice imperfections and microstructure may also play a crucial role in water splitting activity of a photocatalyst. The factors responsible for catalyst deactivation are examined. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: GaFeO3; hydrogen production; Microstructure; Photocatalyst; water splitting

Disordered mesoporous TiO2-xNx+Nano-Au: an electronically integrated nanocomposite for solar H-2 generation - Sivaranjani, Kumarsrinivasan; Rajaambal, Sivaraman; Das, Tanmay; Roy, Kanak; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
We report on H-2 generation by photocatalysis driven by simulated white light by electronically integrated Au nanoparticles with multifunctional, disordered mesoporous TiO2-xNx (Au-NT) nanocomposites. Solar H-2 generation (1.5 mmolh(-1)g(-1)) from aqueous methanol has been demonstrated with Au-NT nanocomposites. The water splitting activity of Au-NT is attributed to the 21.1 ps lifetime of charge carriers observed from fluorescence lifetime measurements, which indicates a high electron-injection efficiency from nano-Au to the conduction band of TiO2, and hence charge separation as well as utilization. This is directly supported by the observation of a high photoluminescence emission intensity with Au-NT that highlights the energy transfer from nano-Au to TiO2. The p-n heterojunction observed between the Au (001) and TiO2 (101) facets helps to-wards the higher charge separation and their utilization. A low mesochannel depth (< 10 nm) associated with disordered mesoporous TiO2-xNx helps the charge carriers to move towards the surface for redox reactions and hence charge utilization. Visible-light absorption, as a result of the surface plasmon resonance of nano-Au, is observed in a broad range between 500 and 750 nm, which helps in harvesting visible-light photons. Finally, electronically integrated nano-Au with TiO2-xNx in Au-NT is evident from Raman and X-ray photoelectron spectroscopy measurements. All of these factors help to achieve a high rate of H-2 production. It is likely that a higher rate of H-2 production than that reported here is feasible by strategically locating Au clusters in porous TiO2 to generate hot spots through electronic integration.
Keywords: heterogeneous catalysis; Hydrogen; mesoporous materials; photochemistry; water splitting

Genesis of enhanced photoactivity of CdS/Ni-x nanocomposites for visible-light-driven splitting of water - Devi, Suman; Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narencira M. (International Journal of Hydrogen Energy, 2014)
A series of CdS/Ni-x nanocomposite photocatalysts, containing ca. 0.6-15 wt% Ni, were synthesized using a one-step hydrothermal method and characterized for their crystallographic, morphological, interfacial, and optical properties. Rietveld refinement of powder XRD data revealed the coexistence of wurtzite (hexagonal) and zinc blende (cubic) phases of CdS in ratios dependent on Ni content. Only a fraction of Ni existed as a secondary phase of NiS while the majority occupied the lattice positions of hexagonal CdS. Whereas up to 10-fold enhancement in H-2 evolution compared with pure CdS was observed for samples containing similar to 1.5-4.5 wt% Ni, samples with smaller or larger Ni content displayed poor activity for visible-light-induced splitting of water in presence of sulfide-sulphite ions as sacrificial electron donors. In contrary to recent findings, our study reveals that the enhanced CdS photoactivity is not a result of charge transfer between p-type NiS and n-type CdS, Ni-induced visible-region absorbance, or the coating of CdS particles by non-photoactive NiS. Instead, the preparation-dependent hexagonal/cubic CdS phase boundaries and particle morphology may play a crucial role. Additionally, certain Ni-doping-induced sub-bandgap shallow energy levels contribute to charge carrier separation. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS/Ni-x nanocomposites; Dominant hexagonal facets; Enhanced photoactivity; Hydrogen evolution; Phase boundary effects; water splitting

Recent developments in solar H-2 generation from water splitting - Rajaambal, Sivaraman; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2015)
Hydrogen production from water and sunlight through photocatalysis could become one of the channels, in the not-so-distant future, to meet a part of ever growing energy demands. However, accomplishing solar water splitting through semiconductor particulate photocatalysis seems to be the `Holy Grail' problem of science. In the present mini-review, some of the critical strategies of semiconductor photocatalysis are focused with the aim of enumerating underlying critical factors such as visible light harvesting, charge carrier separation, conduction and their utilization that determine the quantum efficiency. We attempted to bring out the essential requirements expected in a material for facile water splitting by explaining important and new designs contributed in the last decade. The newly emerged designs in semiconductor architecture employing nanoscience towards meeting the critical factors of facile photocatalysis are elucidated. The importance of band gap engineering is emphasized to utilize potential wide band gap semiconductors. Assistance of metal nanostructures and quantum dots to semiconductors attains vital importance as they are exuberant visible light harvesters and charge carrier amplifiers. Benevolent use of quantum dots in solar water splitting and photoelectrochemical water splitting provides scope to revolutionize the quantum efficiency by its multiple exciton generation features. A list of drawbacks and issues that hamper the much needed breakthrough in photocatalysis of water splitting is provided to invite attention to address them and move towards sustainable water splitting.
Keywords: Hydrogen; nanomaterial; Photocatalysis; quantum dot; Semiconductor; visible light; water splitting

Synthesis of Sn-containing anatase (TiO2) by sol-gel method and their performance in catalytic water splitting under visible light as a function of tin content - Tangale, N. P.; Niphadkar, P. S.; Samuel, V.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Materials Letters, 2016)
Sol-gel route was employed to prepare a series of Sn-containing anatase with different molar (Ti/Sn) ratios ranging from 49 to 1. Samples were characterized by powder XRD, UV-vis, XPS, SEM, EDAX, low temperature N-2 sorption technique and Raman Spectroscopy. Except anatase phase, no other crystalline phase was observed when Ti/Sn molar ratio was varied from 49 to 9 and for Sn free sample. However, further decrease in the ratio lead to the appearance of additional SnO2 phase whose peak intensities were increased with the increase in the tin content. Irrespective of tin content, all samples showed red-shift in UV-vis spectra. Moreover, samples showed Raman shift to higher vibration side from 143 cm(-1) to 147 cm(-1) indicating the doping of Sn2+ into TiO2. By virtue of low band gap, anatase crystallite size and an absence of XRD visible SnO2, ST (19) has shown maximum photocatalytic activity upon 1 wt% Pt loading. It has exhibited the highest rate (0.1264 mmole/g/h) for visible light induced hydrogen evolution by water splitting. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Sn2+ doped titania; SnO2/TiO2; Sol-gel preparation; visible light; water splitting

Co-catalytic metal oxide nanoparticles decorated silicon/hematite core shell nanowire arrays as efficient photo electrodes for water splitting - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ChemistrySelect, 2017)
By looking global energy demands, development of highly efficient stable semiconductor photoelectrodes for photoelectrochemical (PEC) water splitting is highly desirable. Herein, we have fabricated co-catalytic nanoparticles decorated Silicon nanowire (SiNWs)/Hematite(Fe2O3) core sell structures as photo anodes and studied the PEC water oxidation properties. As, Fe2O3 possess weak oxidation kinetics, decoration of NiO and Co3O4 nanoparticles on SiNW/Fe2O3 by hydrothermal method, which acts as co-catalysts to improves the water oxidation reactions. It was found that decoration of Co3O4 nanoparticles enhances the photocurrent up to 2.6 times, whereas for NiO nanoparticles improvement is of 1.5 times when compared to the undecorated electrodes. Along with enhancement of photocurrents, it also shows shift of onset potentials. The effect of the co-catalytic nanoparticles on the enhancement of photocurrent and charge transfer resistance at the interface of electrode-electrolyte have been studied by electrochemical impedance spectroscopy. Further, flat band potentials of the photo electrodes have been measured by using Mott-schottky analysis.
Keywords: Co-catalysts; photo anodes; Photoelectrochemical cell; silicon nanowires; water splitting

Marginally hydrogenated triphasic titania nanotubes for effective visible-light photocatalytic hydrogen generation - Preethi, Laguduva K.; Mathews, Tom; Walczak, Lukasz; Gopinath, Chinnakonda S. (Energy Technology, 2018)
We report the first demonstration of hydrogen-annealed triphase TiO nanotubes (anatase-rutile-brookite) (T-ARB) as a visible-light-active photocatalyst for water splitting with high quantum efficiency. As-synthesized T-ARB was annealed under hydrogen atmosphere at 250 and 4508 degrees C for 2 h. We found that the tubular structures were retained in the hydrogenated TiO2 samples. It was observed that the concentrations of Ti3+ and the oxygen vacancies and their distribution significantly increased with respect to the hydrogen annealing temperature. Such changes in defects were found to be critical in enhancing the photocatalytic activity of the hydrogen-annealed triphase TiO2 nanotubes. The triphase TiO2 nanotubes hydrogen annealed at 450 degrees C were 16 times more efficient than pristine TiO2. Such an increase in the photocatalytic activity was explained by a triphase band diagram with defect states below the conduction band of each phase, which facilitated visible-light activity and easy transfer of charge carriers from one phase to another. Our study showed that the well-designed multiphase construction with oxygen vacancies enhanced the photocatalytic activity tremendously owing to the presence of a higher number of phase junctions.
Keywords: charge transfer; Defects; Hydrogenation; titania; water splitting

Pt - g-C3N4 - (Au/TiO2): electronically integrated nanocomposite for solar hydrogen generation - Devaraji, Perumal; Gopinath, Chinnakonda S. (International Journal of Hydrogen Energy, 2018)
A potential nanocomposite photocatalyst was designed by integrating Pt nanoclusters (co catalyst and electron sink) with graphitic carbon nitride (g-C3N4 (gcn)) (charge diffusion) and 0.5 wt % Au containing Au-TiO2 (AuT) (plasmonic on semiconductor) for solar water splitting (SWS). Variety of Pt-gcn-AuTiO2 compositions has been evaluated for SWS under one sun conditions. Complexity of the photocatalyst was increased systematically from Au-TiO2, gcn-TiO2 to Pt-gcn-Au-TiO2 to explore the influence of different combinations. Electronic integration of charge separation/diffusion component (gcn) with light absorbing sensitizer components (Au and gcn), and co-catalyst (Pt) seems to be the critical factor to improve hydrogen yield (HY) or overall efficiency. Although addition of gcn increase the HY of composites, there is no SWS activity observed on bare TiO2 or gcn. Au or Pt on gcn enhances the charge separation effectively and interface between Au and/or Pt with gcn works as the Schottky barrier. A monodispersion of Au over TiO2 and Pt nanoclusters over gcn/AuTiO2 composite lead to the maximum solar hydrogen yield (1.52 mmol/h g) with an apparent quantum yield (AQY) of 7.5%. Photoelectron and photoluminescence spectral studies confirm the electron transfer from Au to gcn, and Au and/or gcn to titania. A thorough physico-chemical investigation of various composites underscores the electronic integration aspects of the nanocomposite towards storage of electrons in the Pt co-catalyst and hence an effective charge separation and an increase in AQY. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electronic integration; Photocatalysis; Schottky barrier; Solar hydrogen; water splitting

Direct thermal polymerization approach to N-rich holey carbon nitride nanosheets and their promising photocatalytic H-2 evolution and charge-storage activities - Antil, Bindu; Kumar, Lakshya; Reddy, K. P.; Gopinath, C. S.; Deka, Sasanka (ACS Sustainable Chemistry & Engineering, 2019)
Energy conversion and energy storage are two crucial challenges in green chemistry that have attracted tremendous attention for the last several decades. In this work, we have addressed both issues by synthesizing nitrogen-rich, few-layer-thick holey graphitic carbon nitride (g-C3N4) nanosheets by a simple, novel, direct thermal polymerization method, which is found to be very good in photocatalytic H-2 evolution reaction (energy-conversion) and charge-storage supercapacitor (energy-storage) applications. This as-synthesized conjugated polymer semiconductor (obtained stoichiometry C3N4.8) with unique structural and morphological advantages exhibits superior photocatalytic water splitting activity to H-2 evolution (2 620 mu mol h(-1) g(-1)) without the help of any cocatalysts under visible light in the presence of 20% triethanolamine (TEOA). The calculated apparent quantum yield is 8.5% at 427 nm, and the rate of photocatalytic hydrogen generation remained constant for nine consecutive catalytic cycles (9 h photocatalysis). The present material also shows electrochemical double layer capacitor (EDLC) behavior in alkaline electrolyte, where a symmetric coin cell device consisting of this electrode material without any large area support or conductive filler delivers high specific capacitance (275 F g(-1)), energy density (30 Wh kg(-1)), and power density (6651 W kg(-1)), and the supercapacitor cell can retain >98% capacitance efficiency up to 10 000 measured cycles at various current densities.
Keywords: g-C3N4; Hydrogen evolution; nanosheets; Photocatalyst; supercapacitor; water splitting

Electronic integration and thin film aspects of Au-Pd/rGO/TiO2 for improved solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala P.; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2019)
In the present work, we have synthesized noble bimetallic nanoparticles (Au-Pd NPs) on a carbon-based support and integrated with titania to obtain Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2 nanocomposites using an ecofriendly hydrothermal method. Here, a 1:1 (w/w) Au-Pd bimetallic composition was dispersed on (a) high-surface-area (3000 m(2) g(-1)) activated carbon (Au-Pd/C), prepared from a locally available plant source (in Assam, India), and (b) reduced graphene oxide (rGO) (Au-Pd/rGO); subsequently, they were integrated with TiO2. The shift observed in Raman spectroscopy demonstrates the electronic integration of the bimetal with titania. The photocatalytic activity of the above materials for the hydrogen evolution reaction was studied under 1 sun conditions using methanol as a sacrificial agent in a powder form. The photocatalysts were also employed to prepare a thin film by the drop-casting method. Au-Pd/rGO/TiO2 exhibits 43 times higher hydrogen (H-2) yield in the thin film form (21.50 mmol h(-1) g(-1)) compared to the powder form (0.50 mmol h(-1) g(-1)). On the other hand, Au-Pd/C/TiO2 shows 13 times higher hydrogen (H-2) yield in the thin film form (6.42 mmol h(-1) g(-1)) compared to the powder form (0.48 mmol h(-1) g(-1)). While powder forms of both catalysts show comparable activity, the Au-Pd/rGO/TiO2 thin film shows 3.4 times higher activity than that of Au-Pd/C/TiO2. This can be ascribed to (a) an effective separation of photogenerated electron-hole pairs at the interface of Au-Pd/rGO/TiO2 and (b) the better field effect due to plasmon resonance of the bimetal in the thin film form. The catalytic influence of the carbon-based support is highly pronounced due to synergistic binding interaction of bimetallic nanoparticles. Further, a large amount of hydrogen evolution in the film form with both catalysts (Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2) reiterates that charge utilization should be better compared to that in powder catalysts.
Keywords: bimetal; Photocatalysis; surface plasmon resonance; TiO2; water splitting

Glycine-induced electrodeposition of nanostructured cobalt hydroxide: a bifunctional catalyst for overall water splitting - Shilpa, Nagaraju; Nadeema, Ayasha; Kurungot, Sreekumar (ChemSusChem, 2019)
Herein, an interconnected alpha-Co(OH)(2) structure with a network-like architecture was used as a bifunctional electrocatalyst for the overall water splitting reaction in alkaline medium. The complexing ability of glycine with a transition metal was exploited to form [Co(gly)(3)](-) dispersion at pH 10, which was used for the electrodeposition. High-resolution TEM, UV/Vis-diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy were used to confirm that the as-synthesized materials had an alpha-Co(OH)(2) phase. The electrocatalytic oxygen and hydrogen evolution activity of the glycine-coordinated alpha-Co(OH)(2) was found to be approximately 320 and 145 mV, respectively, at 10 mA cm(-2). The material required approximately 1.60 V (vs. reversible hydrogen electrode; RHE) to achieve the benchmark of 10 mA cm(-2) for overall water splitting with a mass activity of approximately 63.7 A g(-1) at 1.60 V (vs. RHE). The chronoamperometric response was measured to evidence the stability of the material for overall water splitting for up to 24 h. Characterization of the catalyst after the oxygen and hydrogen evolution reactions was performed by XPS and showed the presence of a Co-II/Co-III oxidation state.
Keywords: cobalt; Electrochemistry; heterogeneous catalysis; Hydrogen; water splitting

Stress-induced electronic structure modulation of manganese-incorporated Ni2P leading to enhanced activity for water splitting - Sarkar, Shreya; Dheer, Lakshay; Vinod, C. P.; Thapa, Ranjit; Waghmare, V. Umesh; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
The cornerstone of the emerging hydrogen economy is hydrogen production by water electrolysis with concomitant oxygen generation. Incorporating a third element in metal phosphides can tune the crystalline and electronic structure, hence improving the electrocatalytic properties. In this work, Mn-doped Ni2P with varying ratios of Mn and Ni has been explored as excellent catalysts for water splitting. A complete cell made of the best catalyst Ni1.5Mn0.5P electrodes showed low voltage of 1.75 V at a current density of 10 mA cm(-2) due to enhanced electrical conductivity, induction of tensile stress, enhanced electrochemical surface area, and increased electric dipole upon Mn incorporation.
Keywords: Electronic Structure; hydrogen evolution reaction; Oxygen Evolution Reaction; phosphides; water splitting

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting

Rationally designed, efficient, and earth-abundant Ni-Fe cocatalysts for solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala Prabhakar; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2021)
Developing highly efficient and affordable catalysts for solar hydrogen (H-2) generation is crucial, and employing a cocatalyst from earth-abundant elements has a critical role to play. In this context, different compositions of earth-abundant Ni-Fe alloy (1:1, 1:3, and 3:1) have been prepared by hydrothermal method; subsequently, 1 wt % of these Ni-Fe cocatalysts were integrated with TiO2-P25 and thoroughly characterized. The resultant catalysts have been evaluated for solar H-2 production, in powder and thin film forms, under one sun condition and in direct sunlight. Interestingly, all the catalysts in the thin film form exhibit superior hydrogen yield (HY), up to 27 times higher activity than its powder counterpart. Among the photocatalysts, Ni-Fe/TiO2 (3:1 = Ni/Fe; NFT31) composition exhibits the best HY in thin film (8.27 mmol.h(-1).g(-1)) and exceeds all other compositions of catalyst. It is also to be reported that HY measured for the powder form with 1 mg shows 3-17 times higher activity than that measured with 25 mg. This is mainly attributed to effective solar light absorption with a smaller amount of photocatalyst either spread over large area in a thin film form or well-dispersed in suspension forms. Furthermore, the enhanced activity obtained with Ni-Fe/TiO2 photocatalysts is also ascribed to strong electronic integration of Ni-Fe cocatalyst with TiO2 and higher performance obtained with a thin film is attributed to increased charge carrier generation and subsequent charge separation and effective utilization. A decrease in work function of TiO2 by 0.6 eV was observed after its integration with cocatalyst in NFT31.
Keywords: Cocatalyst; Hydrogen; Ni-Fe alloy; solar energy; TiO2; water splitting

Co-Ni layered double hydroxide for the electrocatalytic oxidation of organic molecules: an approach to lowering the overall cell voltage for the water splitting process - Shilpa, Nagaraju; Pandikassala, Ajmal; Krishnaraj, Perayil; Walko, Priyanka S.; Devi, R. Nandini; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2022)
Electrocatalytic oxidation of simple organic molecules oilers a promising strategy to combat the sluggish kinetics of the water oxidation reaction (WOR). The low potential requirement, inhibition of the crossover of gases, and formation of value-added products at the anode are benefits of the electrocatalytic oxidation of organic molecules. Herein, we developed cobalt-nickel-based layered double hydroxide (LDH) as a robust material for the electrocatalytic oxidation of alcohols and urea at the anode, replacing the WOR. A facile synthesis protocol to form LDHs with different ratios of Co and Ni is adapted. It demonstrates that the reactants could be efficiently oxidized to concomitant chemical products at the anode. The half-cell study shows an onset potential of 1.30 V for benzyl alcohol oxidation reaction (BAOR), 1.36 V for glycerol oxidation reaction (GOR), 1.33 V for ethanol oxidation reaction (EOR), and 1.32 V for urea oxidation reaction (UOR) compared with 1.53 V for WOR. Notably, the hybrid electrolyzer in a full-cell configuration significantly reduces the overall cell voltage at a 20 mA cm(-2) current density by similar to 15% while coupling with the BAOR, EOR, and GOR and similar to 12% with the UOR as the anodic half-cell reaction. Furthermore, the efficiency of hydrogen generation remains unhampered with the types of oxidation reactions (alcohols and urea) occurring at the anode. This work demonstrates the prospects of lowering the overall cell voltage in the case of a water electrolyzer by integrating the hydrogen evolution reaction with suitable organic molecule oxidation.
Keywords: electrocatalytic oxidation; energy conversion; imidazole mediated; Layered compounds; water splitting

Electrochemically tuned synergistic nano-interface of a tertiary Ni(OH)(2)-NiO(OH)/NixP heterojunction material for enhanced and durable alkaline water splitting - Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemistrySelect, 2022)
Making water splitting cheaper is the need of the hour.The present work reports a nickel-based, non-precious catalytic system, synthesized by a two-step electrodeposition (ED) process followed by a short-term heat treatment. The Ni(OH)(2)-NiO(OH)/NixP heterojunction has been synthesized and optimized through an unprecedented, energy-conserving method to achieve its best OER performance. Further, it has been carefully tuned for the first time by thoroughly optimizing the ED parameters to exhibit Hydrogen Evolution Reaction (HER). At high current regimes, the performance surpassed that of the Ru/C and Pt/C (>= 500 mA and >= 600 mA) respectively. The full cell electrolyzer configuring NOPO||NOPH further establishes the supremacy of the present electrocatalysts over the benchmark Ru/C||Pt/C. Moreover, the present electrocatalyst displayed 60 and 70 hours of HER and OER performances at -100 mA and 100 mA currents respectively. In short, this work is an example that illustrates how a single chemical system gets to exhibit two complementary catalytic behaviors that is, water oxidation and reduction when certain synthetic parameters are meticulously optimized.
Keywords: Electrodeposition; heterojunction; Ni(OH)(2)-NiO(OH); NixP; non-precious metal; water splitting

Facile, sustainable and unassisted plain water oxidation on Au/Ce0.9Ti0.1O2 nanorods in direct sunlight - Dubey, Anjani; Mishra, Abhaya Kumar; Negi, Sanjay Singh; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2022)
Impressive rate of solar water oxidation to molecular oxygen (O-2) has been demonstrated on nanorods (NRs) of Ce0.9Ti0.1O2 (CT-NR) and Au-deposited CT-NR (Au-CT-NR) photocatalysts with a sacrificial agent (Fe3+) and in plain water in one sun condition, direct sunlight and with lambda >= 455 nm. Probably the highest 0 2 yield of 11 mmol/h.g was observed with Au-CT-NR thin film in plain water in direct sunlight, with no sacrificial agent or applied potential. Photoelectrochemical measurements demonstrate a marked reduction in oxidation onset potential of Au-CT-NR by 150 mV with stable photocurrent (0.75 mA/cm(2)), compared to CT-NR (0.23 mA/cm(2)), indicating the operative of plasmon-induced resonant energy transfer (PIRET) process. Effective electron quenching by nanogold and hence low recombination in the depletion region is a critical step for the observation of a high rate of oxygen evolution. In addition to this, a predominant change in the nature of the valence band from O-2p dominated on CeO2 to Ce-4f dominated with CT-NR (due to Ti4+ introduction in CeO2), the efficient light absorption of photocatalysts in thin-film form, functional and effective PIRET process, and facile E-F alignment, enhances the oxygen evolution with Au-CT-NR in direct sunlight and make it highly sustainable. A possible mechanism of water oxidation is proposed from the observed experimental findings.
Keywords: ceria; Electronic integration; Photocatalysis; thin film; water splitting

Aqueous glycerol to glyceric acid and green hydrogen by visible-light-driven photocatalysis with Ni/Co(PO4)2-TiO2: parallel utilization of holes and electrons - Nivedhitha, Thazhath R.; Bajpai, Himanshu; Oommen, Jiffin Varghese; Abraham, Athira; Chauhan, Inderjeet; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2024)
Replacing the kinetically sluggish oxygen evolution reaction (OER) with the oxidation of an abundantly available organic molecule to value-added product(s) (VAPs) at low voltage along with the hydrogen evolution reaction (HER) is a big challenge in water splitting, either by electrolysis or sunlight-driven photocatalysis. Glycerol oxidation to a VAP is kinetically fast, compared to an OER, and offers hope to enhance sunlight-driven water splitting to hydrogen by the concurrent utilization of holes and electrons. Mixed bimetal phosphates of Co and Ni (CoxNiy(PO4)(2) (CoNiP)) with different Co:Ni ratios (10:0, 7:3, 5:5, 3:7, and 0:10) were integrated with TiO2 to generate final photocatalyst composites (x wt % CoNiP with TiO2) and employed for concurrent photocatalytic HER and glycerol oxidation. Irrespective of the weight ratios of CoNiP and TiO2, any TiO2-CoNiP composite showed better photocatalytic activity for the HER and glycerol oxidation compared to virgin TiO2. The highest HER as well as selectively generated glyceric acid yield was observed to be 54 and 67 mmol/g, respectively, after 25 h of reaction under 1 sun conditions with TiO2-CoNiP-5:5. An increase in catalytic activity can be attributed to the formation of p-n heterojunctions of the constituent component along with uniform distribution of CoNiP to effectively utilize the charge carriers for redox reactions. Highly selective oxidation of glycerol to glyceric acid (85%), along with other minor products, is also demonstrated, which offers further scope to use solar light to generate VAPs in a sustainable manner. A simple comparison of H-2 yield and all oxidized products together indicates the better utilization of holes for the latter, and hence, there is scope to increase HER and possibly the whole photocatalytic activity.
Keywords: biomass component; earth-abundantmaterial; energy conversion; organicvalorisation; water splitting

Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting

Bifunctional nanoelectrocatalyst: semi-amorphous cobalt tungstate-based nanocomposites surpassing amorphous and crystalline counterparts - Dev, Sahil; Nagappan, Sreenivasan; Kundu, Subrata; Mukherjee, Shatabdi Porel (ACS Applied Materials & Interfaces, 2025)
Electrocatalytic water splitting to hydrogen and oxygen is considered to be one of the significant routes for future renewable energy conversion. Therefore, the development of unique, efficient, and cost-effective bifunctional electrocatalysts, which can perform both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is critical for the accessible utilization of renewable energy. The increasing overall efficiency of the water-splitting reaction is pivotal for sustainable energy conversion and hydrogen production. Herein, we present a facile solution-based synthesis route to control the crystallinity of the cobalt tungstate (CoWO4) nanomaterials to amorphous, semiamorphous, and crystalline phases and further exploit these nanomaterials as bifunctional electrocatalysts for the HER, OER, and overall electrochemical water splitting reaction. Notably, the semiamorphous cobalt tungstate nanomaterials show a remarkable surface area of approximately 150 m(2)/g, the highest reported for CoWO4-based materials, and demonstrated superior activity for both the OER and HER and outstanding stability over the amorphous and crystalline counterparts. Notably, the SemiAmp||SemiAmp electrolyzer demonstrated a better performance for overall water splitting than the commercial RuO2||Pt/C electrolyzer.
Keywords: amorphous; CoWO4; electrocatalyst; HER; Nanocomposite; OER; water splitting

Mesoporous Fe2O3-TiO2 integrated with plasmonic Ag nanoparticles for enhanced solar H2 production - Mani, Sunesh S.; Rajendran, Sivaraj; Saju, Simi; Babu, Bindhya M.; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2025)
Present work describes a sol-gel assisted one-pot synthesis of mesoporous Fe2O3-TiO2 nanocomposites (TiFe) with different Ti : Fe ratios, and fabrication of Ag-integrated with TiFe nanocomposites (TiFeAg) by a chemical reduction method and demonstrated for high solar H2 generation activity in direct sunlight. Enhanced solar H2 production is attributed to the light absorption from entire UV+Visible region of solar spectrum combined with Schottky (Ag-semiconductor) and heterojunctions (TiO2-Fe2O3), as evidenced from HRTEM and various characterization studies. TiFeAg-2 thin film (1 wt % Ag-loaded TiFe-4) displayed the highest activity with a solar H2 yield of 7.64 mmol h-1g-1, which is 48 times higher than that of bare TiO2 and 5 times higher in thin film form compared to its powder counterpart. Schottky and heterojunctions formed at the interface efficiently separate the charge carriers and increase the hydrogen production activity. The highest H2 production activity of TiFeAg-2 is partly attributed to the heterogeneous distribution of Fe3+ and metallic Ag-species with relatively high Ag/Ti surface atomic ratio. A plausible photocatalytic reaction mechanism on TiFeAg nanocomposite may involve the direct electron transfer from both Fe2O3 and TiO2 to Ag nanoparticles which are subsequently utilized for the reduction of H+ to H2.
Keywords: energy conversion; green hydrogen; Photocatalysis; Solar harvesting; water splitting